Pengaruh Kecerdasan Emosional, Tingkat Pendidikan Dan Karir Terhadap Kinerja Karyawan (Studi Kasus Pada Sales Marketing PT Astra International Daihatsu Cabang Tangerang) - Catur Widayati (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
This study aims to determine the effect of Emotional Intelligence, Education and Career Levels Of Performance (sales marketing case study on PT Astra International Daihatsu Branch Tangerang) using a descriptive approach This research sample is the employee sales force in PT Astra International Daihatsu Branch Tangerang. Using the questionnaire and SPSS analysis. These results indicate that the EQ variable has a positive and significant impact on employee performance variable partial test results (test-t), 0.021 < 0.05, education rate does not affect the performance of employees with a partial test (t-test) 0.452 > 0.05 and career do not affect the performance of employees with a partial test (t-test) 0.095 > 0.05.